Effectiveness and safety of GnRH antagonist originator and generic in real-world clinical practice: a retrospective cohort study - Cao, Mingzhu; Hu, Yuqi; Xiao, Jiaqi; Li, Sichen; Lin, Yanshan; Liu, Jianqiao; Liu, Haiying (Frontiers in Endocrinology, 2024)
Objective: This study aims to determine whether the live birth rates were similar between GnRH antagonist original reference product Cetrotide ® and generic Ferpront ® , in gonadotropin-releasing hormone (GnRH) antagonist protocol for controlled ovarian stimulation (COS).GnRH antagonist protocols. The research was conducted at a specialized reproductive medicine center within a tertiary care hospital, spanning the period from October 2019 to October 2021. Within this timeframe, a total of 924 cycles were administered utilizing the GnRH antagonist originator, Cetrotide ® (Group A), whereas 1984 cycles were undertaken using the generic, Ferpront ® (Group B).Results: Ovarian reserve markers, including anti-Mullerian hormone, antral follicle number, and basal follicular stimulating hormone, were lower in Group A compared to Group B. Propensity score matching (PSM) was performed to balance these markers between the groups. After PSM, baseline clinical features were similar, except for a slightly longer infertile duration in Group A versus Group B (4.43 ± 2.92 years vs. 4.14 ± 2.84 years, P = 0.029). The duration of GnRH antagonist usage was slightly longer in Group B than in Group A (6.02 ± 1.41 vs. 5.71 ± 1.48 days, P < 0.001). Group B had a slightly lower number of retrieved oocytes compared to Group A (14.17 ± 7.30 vs. 14.96 ± 7.75, P = 0.024). However, comparable numbers of usable embryos on day 3 and good-quality embryos were found between the groups. Reproductive outcomes, including biochemical pregnancy loss, clinical pregnancy, miscarriage, and live birth rate, did not differ significantly between the groups.Multivariate logistic regression analyses suggested that the type of GnRH antagonist did not independently impact the number of oocytes retrieved, usable embryos, good-quality embryos, moderate to severe OHSS rate, clinical pregnancy, miscarriage, or live birth rate.The retrospective analysis revealed no clinically substantive significant differences in reproductive outcomes between Cetrotide ® and Ferpront ® when used in women undergoing their first and second COS cycles utilizing the GnRH antagonist protocol.